Ethyl 2-{3-[(2-chloro-1,3-thiazol-5-yl)methyl]-4-nitroimino-1,3,5-triazinan-1-yl}acetate - Sun, Chuan-wen (International Union of Crystallography, 2010)
In the title compound, C(11)H(15)ClN(6)O(4)S, which belongs to the neonicotinoid class of insecticidally active heterocyclic compounds, the six-membered triazine ring adopts an opened envolope conformation. The planar nitro imine group [dihedral angle between nitro and imine groups = 1.07 (7)°] and the thiazole ring are oriented at a dihedral angle of 69.62 (8)°. A classical intramolecular N—H⋯O hydrogen bond is found in the molecular structure. Moreover, one classical intermolecular N—H⋯N and four non-classical C—H⋯O and C—H⋯N hydrogen bonds are also present in the crystal structure. Besides intermolecular hydrogen bonds, the Cl atom forms an intermolecular short contact [3.020 (2) Å] with one of the nitro O atoms.